Can Patient‐Reported Symptoms Be Used to Measure Disease Activity in Systemic Sclerosis?. Issue 10 (29th September 2020) - Ross, Laura; Stevens, Wendy; Wilson, Michelle; Strickland, Gemma; Walker, Jennifer; Sahhar, Joanne; Ngian, Gene-Siew; Roddy, Janet; Major, Gabor; Proudman, Susanna; Baron, Murray; Nikpour, Mandana
Abstract : Objective: To evaluate the association between patient‐reported symptoms and changes in disease activity over time in systemic sclerosis (SSc). Methods: Using data from 1, 636 patients enrolled in the Australian Scleroderma Cohort Study, we used generalized estimating equations to determine the relationship between patient‐reported worsening of Raynaud's phenomenon (RP), skin involvement, and breathlessness in the month preceding each study visit and features of disease activity in the corresponding organ systems. The associations between the following parameters were analyzed: patient‐reported worsening RP and the presence of new‐onset digital pitting and digital ulcers; patient‐reported worsening skin involvement and increasing modified Rodnan skin thickness score (MRSS); new areas of skin involvement and new‐onset joint contractures; patient‐reported worsening breathlessness and deteriorating respiratory functions test (RFT) results, indicated by a 10% decrease in forced vital capacity (FVC) and a 15% decrease in diffusing capacity for carbon monoxide (DLco ), new‐onset interstitial lung disease (ILD), and new‐onset pulmonary arterial hypertension (PAH). Results: We found a significant association between patient‐reported worsening RP and the presence of digital ulcers (odds ratio [OR] 1.53 [95% confidence interval (95% CI) 0.60–0.93]), patient‐reported worsening skin involvement and increasing MRSS (OR 2.10 [95% CI 1.54–2.86]), and worsening patient breathlessness and deteriorating RFTs (FVC OR 2.12 [95% CI 1.70–2.65]; DLco OR 1.97 [95% CI 1.34–2.02]), new‐onset ILD (OR 1.91 [95% CI 1.40–2.61]), and new‐onset PAH (OR 5.08 [95% CI 3.59–7.19]). Conclusion: These results demonstrate that patient‐reported symptoms are associated with clinically meaningful changes in disease activity in patients with SSc. This suggests that when objective measures of change in disease status are unavailable, patient‐reported symptoms could be used to indicate a change in SSc disease activity.